Analysis of genetic variability in F2 interspecific hybrids of mung bean (Vigna radiata) using inter-retrotransposon amplified polymorphism marker system (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fatmawati Y, Setiawan AB, Purwantoro A, Respatie DW, Teo CH. 2021. Analysis of genetic variability in F2 interspecific hybrids of mung bean (Vigna radiata) using inter-retrotransposon amplified polymorphism marker system. Biodiversitas 22: 4880-4889. Mung bean (Vigna radiata L. Wilczek) categorized as one of the pivotal annual crops of Vigna genera is commonly cultivated in rotation with the cereal crops during the drought season. Conversely, to ameliorate its stunted productivity, the interspecific hybridization technique has been introduced between the mung bean and the common bean to promote genetic improvement with the breeding projects in Indonesia. However, since mung bean is a self-pollinated crop and has a narrow genetic base, the selection and improvement of a specific trait using marker-assisted selection is more challenging. Hence, a precautionary investigation is imperative to evaluate the progenies resulting from interspecific hybridization using an ideal marker. This study aimed to investigate the genetic variability of the F2 population of the interspecific mung bean hybrids using retrotransposon-based markers, particularly Inter-Retrotransposon Amplified Polymorphism (IRAP) markers. In this study, we identified retrotransposon from the mung bean genome and determined the Long Terminal Repeat (LTR) sequence using the LTR Finder. The IRAP primers were designed from a conserved region of the LTR sequence. One hundred of the F2 interspecific hybrids generated from the crossing between mung bean and common bean were successfully discriminated by IRAP markers. The IRAP marker showed high heterozygosity and moderate Polymorphic Information Content (PIC) values. The IRAP markers were able to detect genetic variability in the F2 progenies resulting from the interspecific hybridization. Cluster analysis showed that 100 of the F2 progenies were grouped into three clusters. This study demonstrated that retrotransposon-based markers can offer an effective approach for evaluating the segregation in the F2 population of intercross hybrids in the mung bean.
Keywords: Interspecific hybridization; IRAP marker; genetic diversity; segregation distortion